Testing of Water Smart Meters Under Various Conditions - Ben-Mansour R.; Alsarkhi A.; Alshehri A.; Algazal E.; Alomar A.; Alhemdda I. (EPJ Web of Conferences)
The accuracy Smart water meters are being widely used across developed and developing countries in order to avail accurate and updated billing for the consumers and provide more accurate data for the water companies to manage their water networks. The accuracy and reliability of these smart meters under different scenarios such as line pressures, existence of air bubbles in the water pipes, existence of sand particles and different water salinity and meter idle time; are extremely important for both consumers and suppliers. SASO and ME-KFUPM have worked together for the last two years to carry out rigorous tests according to recognized standards to investigate the accuracy of these meters under various conditions mentioned above. The results of these investigations have revealed interesting findings regarding the accuracy and reliability of both Ultrasound and electromagnetic smart meters across various pressure levels (0.5-2.5 bars), different flow rates (Q1 to Q3), and in measuring transient pressures and flow rates. Notably, when air bubbles were introduced into the flow stream, all meter types exhibited intriguing outcomes. These findings contribute to our understanding of the capabilities of these meter types in diverse scenarios.